Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1007/bfb0082792
|View full text |Cite
|
Sign up to set email alerts
|

The universality theorems on the classification problem of configuration varieties and convex polytopes varieties

Abstract: The results which we present here form the part of guiding by A.M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
209
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(221 citation statements)
references
References 2 publications
4
209
0
Order By: Relevance
“…Extending results of Mnëv [16] by using techniques described in [3] one finds (see [1,Cor. 9.5.11]) that there is a polynomial (Karp-)reduction of the problem to decide whether a system of linear inequalities has an integral solution to problem (S).…”
Section: Remarksmentioning
confidence: 77%
“…Extending results of Mnëv [16] by using techniques described in [3] one finds (see [1,Cor. 9.5.11]) that there is a polynomial (Karp-)reduction of the problem to decide whether a system of linear inequalities has an integral solution to problem (S).…”
Section: Remarksmentioning
confidence: 77%
“…Some of the traditional ETR results are actually universality theorem; for example, Mnëv [34] showed that any semi-algebraic set is stably equivalent to the realization space of a pseudoline arrangement. We do not want to define stable equivalence explicitly (see [39] for a detailed discussion), but roughly speaking it means that the two sets look very similar algebraically.…”
Section: Issues Of Precisionmentioning
confidence: 99%
“…Many computational problems in geometry, graph drawing and other areas can be shown decidable using the (existential) theory of the real numbers; this includes the rectilinear crossing number, the Steinitz problem, and finding a Nash equilibrium; what is less often realized-with some exceptions-is that the existential theory of the reals captures the computational complexity of many of these problems precisely: deciding the truth of a sentence in the existential theory of the reals is polynomial-time equivalent to finding the rectilinear crossing number problem [3], solving the Steinitz problem [34,4], finding a Nash Equilibrium [43], recognizing intersection graphs of convex sets and ellipses [42], recognizing unit disk graphs [32] and many other problems. 1 In this paper we try to further substantiate this claim by showing that some well-known Euclidean realizability problems have the same complexity.…”
Section: Introductionmentioning
confidence: 99%
“…(In fact, universality theorems [7,8] suggest, but do not prove, that it is probably at least NP-hard and PSPACE-hard, if not harder.) Thus, it is interesting to find efficiently computable subclasses of graphs which contain the graphs of simple polytopes.…”
Section: Polynomially Computable Classes Of Almost-polytopal Graphsmentioning
confidence: 99%